Legal challenges posed by the war on drugs and the fight against organized crime in Colombia (2020)
This article aims to highlight the evolution of crime in Colombia and how it is a drawback to the current understanding of the applicability of international humanitarian law. The peace agreement between the Revolutionary Armed Forces of Colombia-FARC, the government and the emerging armed actors are a challenge to Colombian law and legal institutions. Accordingly, the article concluded that the use of force by the Colombian government against drug trafficking organizations, or socalled Criminal Gangs-BACRIM, does not seem to be the legal way to combat them since these organizations do not necessarily participate in hostilities, which means that the government has to follow a specific procedure.